2008
DOI: 10.1007/s00259-008-1009-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 18F-fluorodeoxyglucose positron emission tomography for diagnosing disease activity and monitoring therapeutic response in patients with pulmonary mycobacteriosis

Abstract: (18)F-FDG PET is considered to be useful for the diagnosis and evaluation of disease activity along with HRCT findings, and in monitoring response to chemotherapy in patients with PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 20 publications
6
90
0
1
Order By: Relevance
“…FDG-PET is obviously not a test of malignancy but of metabolism. This is also true for solitary pulmonary nodule due to NTM infection (19). Because the present case also demonstrated that a solitary pulmonary nodule due to M. kansasii can exhibit high FDG uptake on FDG-PET imaging, it was difficult to distinguish lung cancer.…”
Section: Discussionmentioning
confidence: 62%
“…FDG-PET is obviously not a test of malignancy but of metabolism. This is also true for solitary pulmonary nodule due to NTM infection (19). Because the present case also demonstrated that a solitary pulmonary nodule due to M. kansasii can exhibit high FDG uptake on FDG-PET imaging, it was difficult to distinguish lung cancer.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, uptake of 18 F-FDG increased when an ineffective drug was given and in the control group. In humans, data by Demura et al 141 indicate that 18 F-FDG-PET could be an important noninvasive method for the diagnosis of latent and active disease that enables management of pulmonary mycobacterial infection as well as for assessment of therapeutic response in patients with pulmonary mycobacteriosis. This study, however, predominantly included patients suffering from nontuberculous pulmonary mycobacteriosis 141 and confirmation of their findings in TB patients are needed.…”
Section: Therapy Monitoring Of Tbmentioning
confidence: 99%
“…In humans, data by Demura et al 141 indicate that 18 F-FDG-PET could be an important noninvasive method for the diagnosis of latent and active disease that enables management of pulmonary mycobacterial infection as well as for assessment of therapeutic response in patients with pulmonary mycobacteriosis. This study, however, predominantly included patients suffering from nontuberculous pulmonary mycobacteriosis 141 and confirmation of their findings in TB patients are needed. Park et al 142 have demonstrated that during anti-TB treatment, some bacillusnegative tuberculomas do not decrease in size or may even keep growing, making it difficult for physicians to decide whether to alter treatment regimens.…”
Section: Therapy Monitoring Of Tbmentioning
confidence: 99%
“…In contrast, increased FDG uptake indicates that the metabolism of the lesion is still high despite the treatment, meaning that the lesion is not responsive to the current treatment, and as such, the treatment method needs to be changed [14,15]. Demura et al [6] reported that in patients with pulmonary tuberculosis, F-18 FDG PET/CT was useful for examining the activity of the tuberculosis and for assessing the treatment response, while Park et al [5] reported that based on the case where a decrease in FDG uptake was observed after treatment, F-18 FDG PET/CT was useful for the assessment of the treatment responses of tuberculoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…F-18 fluorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT), well known for usefulness in assessing malignant tumors, can yield positive results for inflammation sites such as those caused by tuberculosis [4]. The usefulness of F-18 FDG PET/CT in the assessment of the activity of extrapulmonary tuberculosis and of the patient's treatment response was recently reported [5,6].…”
Section: Introductionmentioning
confidence: 99%